2003
DOI: 10.1353/rhe.2003.0006
|View full text |Cite
|
Sign up to set email alerts
|

Academic Life at the Franchise: Faculty Culture in a Rural Two-Year Branch Campus

Abstract: This case study of faculty culture focused on the dynamics of a small, rural, two-year branch campus of a large state university. It reports descriptive themes concerning the isolation and rural location of the campus, its diminutive size, faculty role perspectives, and factors related to faculty role implementation. It provides a portrait of this campus and describes how faculty fulfill their roles in such a setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 6 publications
0
34
0
Order By: Relevance
“…Study after study has found that the majority of community college faculty members find teaching to be a satisfying career; overwhelmingly, faculty report that their greatest satisfaction comes from teaching. Ironically, they also often tell researchers that it is the teaching of the unprepared or underachieving student that is most satisfying (Wolfe and Strange, 2003).…”
Section: Retaining Facultymentioning
confidence: 99%
“…Study after study has found that the majority of community college faculty members find teaching to be a satisfying career; overwhelmingly, faculty report that their greatest satisfaction comes from teaching. Ironically, they also often tell researchers that it is the teaching of the unprepared or underachieving student that is most satisfying (Wolfe and Strange, 2003).…”
Section: Retaining Facultymentioning
confidence: 99%
“…In particular, he found that women faculty teaching secretarial courses had lower status than men teaching business courses. More recently, Wolfe and Strange (2003) noted in their study of a small, rural two-year college branch campus of a university, "Success as a faculty member at Park is a function of differences in a distinctive hierarchy of disciplines, faculty preparation, and credentials, and employment status" (p. 355). Faculty in the humanities and with a terminal degree were the most likely to attain tenure, and most full-time faculty had higher status than part-time faculty, except in particular fields such as business and the technologies.…”
Section: Teaching Areamentioning
confidence: 99%
“…But other than these few activities, the culture and role expectations of community colleges may discourage faculty from engaging in traditional research. A study of faculty culture at a two-year branch campus of a university (Wolfe and Strange, 2003) stressed that working in a community college could be detrimental to conducting the level of research needed for "a progressive academic career ladder," the move "up and out" to another institutional type like a university (p. 360).…”
Section: Research/scholarshipmentioning
confidence: 99%
“…As indicated above, 57 percent of public community colleges are designated as rural. Using the measure of annual unduplicated head count enrollment, rural institutions served 36 percent of all community college enrollments in academic year 2003(Hardy, 2005. Maldanado (2006) found that 42 percent of the fulltime faculty employed by geographically designated community colleges held appointments at rural-serving institutions.…”
mentioning
confidence: 99%